The value of ultrasound-guided surgery for breast cancer. (September 2017) - Arko, Darja; Čas Sikošek, Nina; Kozar, Nejc; Sobočan, Monika; Takač, Iztok
Abstract: Objective: An increasing number of breast-conserving surgeries (BCS) has lead clinicians to the dilemma how to provide patients with the best pathological, short-term and long-term outcomes, while at the same time improving the cosmetic outcome and the patients' quality of life. A proposed solution is the use of intraoperative ultrasound (IOUS) for lesion resection in palpable as well as non-palpable breast cancer. Methods: This review identifies and compares evidence on palpation-guided/wire-guided vs. US-guided localization as well as stand-alone observational IOUS studies published between June 2001 and July 2017, indexed in Medline. A cornerstone of this review is the discussion on technology advancement as well as alternative IOUS approaches and their feasibility in treatment of patients with calcifications and multifocal lesions currently not treated with IOUS localization. Results: In comparison to other available methods, IOUS provided in most studies better rates of clear margins, lower rates of re-excisions as well as better cosmetic outcomes. Currently, there is a lack of available multicenter data on method comparisons as well as several limitations to the use of IOUS. Conclusions: With a comparable follow-up rate of loco-regional recurrences and a higher reported long-term quality of life, IOUS should be a highly regarded method of localization in the planning of BCS.